Increasing Age, the Existence of Comorbidities, and Corticosteroid Treatment in Combination With Antiviral Therapy Prolongs the Recovery of SARS-COV-2-Infected Patients, Measured as the Conversion From Positive to Negative rtPCR: A 239 Patients' Retrospective Study - Zhu, Sheng; Huang, Yaxiong; Tang, Wei; Nussler, Andreas K.; Zheng, Fang (Frontiers in Medicine, 2020)
Background Severe acute respiratory syndrome (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), has become a global pandemic in the past five months. An overall defined treatment has not been yet established. Therefore, it is important to summarize and report treatment experiences and identify patient groups that have a significantly higher risk of an adverse clinical outcome. Methods 239 COVID-19 patients were recruited from Jan 25 to Feb 15, 2020. Demographic, clinical, laboratory, treatment management, and outcome data obtained from patients’ medical records were evaluated. Results Patients who recovered from PCR positive to negative within 2 weeks had significantly lower ESR and higher CRP levels than those recovered over post 2 weeks. During antiviral treatment, COVID-19 patients with older age, comorbidities and corticosteroid treatment required a significantly longer time to turn from PCR positive to negative COVID-19 result. Conclusion PCR tests are of great importance to evaluate the recovery of COVID-19 positive patients, and ESR could be an indirect indicator to monitor SARS-COV-2 activity. Furthermore, our data suggest older age, the existence of comorbidities and corticosteroid treatment of COVID-19 patients during antiviral treatment could prolong the duration of conversion from SARS-COV-2 positive to negative.